Public-Private-Civil Partnership approach for improving disaster risk management and resilience: application in the Balearic Islands - Jaumouillé, Alexandra; Rimlinger, Juliette; Freissinet, Catherine; Muntaner, Margarita Ribas; Moragues, Alexandre; Estrany, Joan; Jiménez, Josué Díaz; Girard, Antonio Bernat; Pujol, Juan Pol (European Journal of Sustainable Development, 2025)
In response to the urgent global and European call for climate action, the C2IMPRESS Horizon Europe project addresses critical data and awareness gaps related to compound extreme weather and climate events. It promotes a shift from hazard-focused approaches to people and place centred strategies for assessing multi-hazard risks, particularly in contexts of weak governance and community vulnerability. Participatory approaches are one possible response and can help strengthen territorial resilience and improve local governance for better risk management in the face of climate change. The Public-Private-Civil Partnership (PPCP) approach, developed by ARTELIA under the C2IMPRESS project in 2023, is part of this dynamic and offers an inclusive model that engages the public and private sectors as well as civil society to address social, economic, and environmental challenges in a coordinated manner. The PPCP approach was tested through the implementation of Labs at Puigpunyent Municipality (Balearic Islands) for the C2IMPRESS project, contributing to the development of the Municipal Emergency Management Plan, including risk mapping, vulnerability assessment, and disaster response measures. The results can guide future operational situations and protocols within the Plan, incorporating local specificities and moving away from standard plans, thus improving and making disaster risk management and resilience more effective. The paper contributes to existing research by focusing on multi-organisational perspectives. On a practical level, it supports hospitals in designing their change strategies and processes jointly and in collaboration with other parties that are part of secondary processes. Keywords: Disaster risk management, Climate change impact, Public-Private-Civil Partnership, Governance, Emergency management Plan, Resilience, Vulnerability, Stakeholders engagement